PENGARUH ASIMETRI INFORMASI TERHADAP BIAYA EKUITAS DAN BIAYA UTANG DENGAN MANAJEMEN LABA SEBAGAI VARIABEL INTERVENING - Jasman Jasman (Jurnal Riset Akuntansi dan Keuangan, 2016)
ABSTRACTThis research aims to investigate the influence of asymmetric information on cost of debt and cost ofequity, and the role of earnings mangement as intervening variable. The research design isquantitative method. The Sample used in this study is property & real estate companies listed inIndonesian Stock Exchange. The result shows that there is no influence of asymmetric information toearnings management. Empirical evidence shows that asymmetric information negatively affect costof equity; on the other hand, asymmetric information does not influence cost of debt. Furthermore,earnings management does not influence cost of equity and cost of debt. Earnings managementcannot be used as an intervening variable in examining the relationship between asymmetricinformation to cost of debt. However, earnings management can be empirically used as anintervening variable in analyzing the relationship of asymmetric information to cost of equity.Keywords: information assymmetry, earnings management, cost of debt, cost of equity